AN APPROACH FOR MULTI-USER ACCESS TO LIBRARY FULL-TEXT CD-ROM DATABASE VIA THE CAMPUS NETWORK - Chen, Ruey-Shun; Yeh, Y.S. (Malaysian Journal of Library and Information Science, 1997)
The Library CD-ROM jukebox with its enormous storage, retrieval capabilities and reasonable price is gradually replacing some of its counterparts. One of the greatest limitations in using the standalone CD-ROM jukebox is that only one user can access the CD-ROM jukebox database at a time. This paper describes the practical design and implementation of a microcomputer-based system with a Novell server that allows multi-user access to the library CD-ROM jukebox database via the campus network. Microcomputers are linked via standard network interfaces like Ethernet, high speed fibre networks and standard protocols (TCP/IP and IP tunnels) to login to a Novell server. Advantages of such a system includes, reduction in waiting time, improved access speed and reducing the damagethrough constant user handling of jukebox CD-ROM devices.